Analysis of Students' Misconceptions Using Three-Tier Diagnostic Test on Straight Motion Material - Linawati, Ela Vika; Suyidno, Suyidno; Miriam, Sarah; Qamariah, Qamariah (Universitas Lambung Mangkurat, 2025)
This study aims to analyze the extent of misconceptions held by students at SMAN 3 Kuala Kapuas regarding the motion of objects and their causes. This study constitutes descriptive research. The methodologies employed for data collection included observation and testing. The instruments employed comprised both test and non-test instruments (questionnaires). The three-tiered diagnostic test was designed to ascertain the extent of student misconceptions. The non-test instrument employed was an interview instrument designed to ascertain the underlying factors contributing to the formation of erroneous beliefs among students. The tools employed consisted of test papers and structured interview protocols. The data pertaining to misconceptions were subjected to both quantitative and qualitative analysis, after which the percentage of students' misconceptions was elucidated through discussion. The population for this study comprised all students enrolled in Class X MIPA at SMAN 3 Kuala Kapuas, while the sample size consisted of 15 students. According to the analysis of the data, the average percentage of misconceptions among students at SMAN 3 Kuala Kapuas is 45.33%. The factors contributing to misconceptions among students include their abilities, the teaching methods employed by teachers, the interactions and communication between teachers and students throughout the learning process, and the student's learning styles. The implications of this study suggest that it influences the learning process and enhances the quality of student comprehension. Furthermore, it facilitates the development of superior instructional materials, such as incorporating illustrations, simulations, or straightforward experiments, which elucidate abstract concepts.